Association Between Plasma Irisin in Mid-Pregnancy and Postpartum Glucose Levels Among Chinese Women. (29th May 2020) - Tang, Nu; Chen, Yajun; Wu, Weijia; Zhang, Jingshu; Tan, Kaiyun; Jing, Jin; Cai, Li
Abstract: Objectives: The association between plasma irisin and glucose levels in general population was controversial and few researches longitudinally explored this correlation. We aimed to examine whether mid-pregnancy irisin was associated with postpartum glucose among Chinese women and explore the potential modifiable factors. Methods: We conducted a prospective cohort study in Guangzhou, China during 2017–2018 and 453 pregnant women (20–28 weeks) were enrolled. At 6–8 weeks after birth, 94 women with gestational diabetes mellitus (GDM) underwent a 75 g oral glucose tolerance test, and the other 359 women had a fasting blood glucose (FBG) test. Multivariable linear regression, quantile regression, and logistic regression analysis were conducted. Results: Mean baseline plasma irisin was 13.73 ng/ml. The prevalence of postpartum impaired fasting glucose (IFG) was 14.35% in all participants. Among women with previous GDM, 23 (24.47%) had impaired glucose tolerance (IGT). We found a significantly negative association between mid-pregnancy irisin and postpartum FBG (β: −0.056 ± 0.024). While quantile regression showed the associations were only significant in high percentiles of FBG (P50 to P95), and the magnitude displayed an increasing trend. In addition, higher baseline irisin was associated with lower risk of postpartum IFG (RR, 0.563; CI, 0.384–0.825). Furthermore, we detected significant interactions between irisin and breastfeeding on FBG and IFG (both Pinteraction < 0.05). But baseline irisin was not significantly associated with postpartum postprandial glucose levels or the risk of IGT in women with GDM. Conclusions: Plasma irisin levels during mid-pregnancy were negatively associated with FBG and IFG at 6–8 weeks postpartum among Chinese women, and stronger associations in women with higher FBG values were observed. Moreover, breastfeeding may modify this relationship. Funding Sources: This work was supported by the National Natural Science Foundation of China (81, 602, 862) and the Sanming Project of Medicine in Shenzhen (SZSM201803061).